Violin improvisation in Afro-Cuban religious ceremonies - Iivari, Ville (fi=Turun yliopisto|en=University of Turku|, 2023)
In this dissertation, I study the violin improvisations performed during Violín a Ochún events, one of the collective celebrations of Santería, a religion practiced in Cuba. The study focuses on different structural organizational models at the basis of improvisation and their attendant cultural meanings and associations. The research aims to expand the study of cognitive and music analytic model-based improvisation into a culture-sensitive direction. Furthermore, I comprehensively present the social, historical and cultural context in which improvisations emerge: one of the main chapters of the research focuses on the phenomenon of the Violín a Ochún, its formation process, content and structure . The study has been carried out using ethnographic methods. A special method of participant observation, the idea of bi-musicality, has been emphasized. The research is a field study, consisting of several phases of fieldwork and analysis. The research material includes forty video-recorded improvisations (and transcriptions of them) from 2007 to 2010, the work of twelve violinists who lived in Havana when the fieldwork phases were carried out. Additionally, the research material contains forty-two interviews, the most recent of which is from 2022. The study indicates that there are both similarities and generation-based differences in the manner in which the violinists exploit the models. The similarities appear especially in relation to the guiding role of the clave pattern. However, its significance is emphasized particularly on son-based improvisations that stress the anticipated harmony. Furthermore, the collectively shared rhythmic-melodic vocabulary is similar in many ways, and it is learned partly when performing on these occasions. On the other hand, there are differences based on the violinist’s generation. The violinists of the older generation more clearly follow the traditional típico style, while the improvisations of the younger violinists reflect more modern currents. This has been influenced by the emergence of systematic music education in post-revolutionary society and new role models among the violinists. However, violinists, regardless of what generation they represent, emphasize the importance of local tradition and the role of improvisation as part of the collective occasion in which interaction with the audience – which participates in several ways in the progress of improvisation – is essential. In addition to guiding musicians, musical models interplay with cultural models and include different cultural meanings and associations that both guide the behaviour of the participants of the Violín a Ochún event and underline commonly shared cultural knowledge.

--- Tutkin väitöskirjassani Kuubassa harjoitettavan santería-uskonnon Violín a Ochún -tilaisuuksissa esitettyjä viuluimprovisaatioita. Tutkimus keskittyy viulistia improvisaation aikana ohjaaviin musiikillisiin rakenteisiin, niin sanottuihin malleihin, sekä niihin liittyviin laajempiin kulttuurisiin merkityksiin ja assosiaatioihin. Tutkimus pyrkii laajentamaan kognitiivista ja musiikkianalyyttista mallipohjaista improvisaatiotutkimusta kulttuurisensitiiviseen suuntaan. Lisäksi yksi tutkimuksen luvuista käsittelee laajemmin esityskontekstia, Violín a Ochún -juhlaa. Tutkimus on useasta Havannaan suuntautuneesta kenttätyömatkasta koostuva etnografinen tutkimus, jossa painottuu bi-musikaalisuuden ajatus osallistuvan havainnoinnin muotona. Tutkimusaineisto kattaa 40 videoitua improvisaatiota (ja niistä tehdyt transkriptiot) yhteensä 12:lta tilaisuuksissa soittaneelta viulistilta. Lisäksi aineistoon sisältyy 42 haastattelua. Tutkimus osoittaa, että viulistien tavoissa hyödyntää musiikillisia malleja on sekä yhtäläisyyksiä että sukupolvien välisiä eroja. Yhtäläisyydet liittyvät clave-rytmisolun huomioimiseen erityisesti son-pohjaisessa musiikissa. Lisäksi viulistien improvisaatioissaan hyödyntämä rytmismelodinen sanavarasto, joka opitaan osittain tilaisuuksissa soittamisen seurauksena, on monilta osin samankaltainen. Toisaalta vanhempaa sukupolvea edustavat viulistit seuraavat selvemmin perinteistä típico-tyyliä, kun puolestaan nuorempien viulistien improvisaatioista heijastuvat vallankumousta seuranneen systemaattisen musiikkikoulutuksen sekä nuorempien viulisti-roolimallien vaikutus. Kaikki viulistit painottavat paikallisen perinteen tärkeyttä ja improvisaation roolia osana kollektiivista tilaisuutta, jonka aikana vuorovaikutus yleisön kanssa on keskeistä. Sen lisäksi, että musiikilliset mallit ohjaavat muusikoita, niiden voidaan nähdä olevan vuorovaikutuksessa kulttuuristen mallien kanssa. Ne sisältävät erilaisia kulttuurisia merkityksiä ja assosiaatioita, jotka ohjaavat tilaisuuteen osallistuvien ihmisten käyttäytymistä ja korostavat yhteisesti jaettua kulttuurista tietoa